A CFD simulation of CLSM filling with piping on Herschel–Bulkley rheological model. Issue 2 (27th March 2018) - Zhang, Xuesong; Yu, Rangang; Chen, Jinping
Abstract : In order to study and predict the flowing behaviour of controlled low-strength material (CLSM) slurry filling with piping transportation, a three-dimensional computational fluid dynamics simulation is carried out based on the Herschel–Bulkley (H-B) rheological model. The simulation is validated by L-pipe flow experiments of CLSM on the flow time and flow pattern. The analysis results show that it is reliable to use the H-B model to simulate the flow of the CLSM slurry. On this basis, simulations are performed to predict the dynamic characteristics of CLSM slurry filling with piping transportation and analyse the velocity distribution and pressure variation in pipeline. The simulation results are consistent with the basic law of power flow, which proves the rationality and effectiveness of the method. The study on the filling characteristics of CLSM slurry pipeline lays a theoretical foundation for the realisation of low-cost, safe and efficient filling of abandoned pipelines.